HOW QUALITY, SATISFACTION AND IMAGE CREATE LOYALTY AT AN INDONESIAN BANKING COMPANY: An Empirical Study in PT. Bank Bukopin, Tbk Malang Branch - Oktiviane, Cunanda Ayu; Hussein, Ananda Sabil (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to examine and explain how service quality, customer satisfaction and corporate image create customer loyalty in Indonesian banking company. The research was conducted in the area of Malang city, the individual customers who have funding product owned PT. Bank Bukopin, Tbk in Malang city. Further convenience sampling technique is used in this research with 150 people. The analysis tools are Partial Least Square (PLS) to determine the pattern and effect relationships between variables in sequence, i.e. endogenous and exogenous variables. The results of the study explained that there is a significant effect between the service quality to the customer satisfaction and corporate image, the corporate image to the customer satisfaction and the customer satisfaction to the customer loyalty Keywords: Service quality, customer satisfaction, corporate image, customer loyalty